Perancangan Sistem Mekanis Alat Pencabut Singkong untuk Optimasi Sistem Panen Bagi Petani Singkong di Kelurahan Borong Loe Kecamatan Bonto Marannu Kabupaten Gowa - Sapta Asmal (Faculty of Engineering UNHAS, 2020)
Cassava which is commonly planted by farmers in Borong Loe Village, Bonto Marannu District, Gowa Regency is local cassava. The time needed from the planting process until the cassava is ready for harvest ± 6-7 months. Cassava crops are sold for various needs such as one of the important food ingredients as a source of carbohydrate intake. The harvesting process used by farmers today is still using the manual method, which is to use hand pulling. so it requires a long time and more energy in extracting the tubers. The absence of tools or technology used in harvesting cassava (cassava), so the use of hands for the harvesting process causes the cassava farmers to easily experience fatigue and complaints of sick hands. Through the Unhas Community Service Program-Community Partnership Program, the appropriate technology is designed and made in the form of a cassava extractor with a mechanization system to facilitate farmers in harvesting their cassava yields. From the results of research and measurement of lift force in the field that has been carried out in the trial the tool is able to change the compressive force of the operator's hand at 334.49 N to lift or pull force of 2000 N